From Charity to Social Protection: Zakat-Based Community Health Intervention for Children with Cerebral Palsy in Indonesia - Nuraini, I'in; Aprillia, Erron Lolha (Potret Pemikiran, 2025)
Studies on Islamic philanthropy have predominantly focused on zakat as an instrument of economic empowerment, while its application as a social protection mechanism in the domain of disability healthcare remains largely underexplored. This study addresses that gap by examining how zakat is institutionally operationalized and socio-religiously understood as social protection for children with cerebral palsy in a context of limited healthcare access. A qualitative intrinsic case study was conducted examining the Jombang Sehat program administered by BAZNAS Jombang Regency, East Java, Indonesia. Data were collected through semi-structured in-depth interviews with program coordinators, physiotherapists, and caregivers of eight enrolled children, complemented by non-participant observation and program documentation review. Data were analyzed using reflexive thematic analysis. Four themes were identified: (1) the institutional operationalization of home-visit physiotherapy and nutrition as a sustained protective intervention; (2) measurable improvements in motor function and nutritional status among beneficiary children; (3) the socio-religious framing of the program within maqasid al-shariah, particularly hifzh al-nafs and hifzh al-nasl; and (4) the formation of social capital and community care networks among beneficiary families. The findings demonstrate that zakat, when deployed with institutional intentionality, can perform preventive, promotive, and transformative social protection functions simultaneously. The study repositions zakat from charity to community-based social protection and establishes BAZNAS as a non-state structural protection actor for disability populations underserved by formal health systems.